Fish/prawn seed rsources and hydrography in the surf and backwater at Cochin - Selvaraj, G S D; Varghese, Molly; Thomas, V J; Khambadkar, L R (Indian Journal of Fisheries, 2011)
Fish/prawn seed rsources and hydrography in the surf and backwater at Cochin